Integration of natural sciences content into professional training of future doctors - Kozlovska, Iryna; Paykush, Marianna; Pastyrska, Iryna (Lviv Politechnic Publishing House, 2016)
The article deals with the problem of integration of natural sciences content into professional training of future doctors. The aim of the article is defined as methodological substantiation of the expediency of integration of natural sciences content into the professional training of future healthcare professionals. The authors define special features of natural sciences knowledge and of natural sciences training of a future doctor, special features of teaching natural sciences, and substantiate possibilities of integration of the content of the natural sciences component into professional training of future medical workers. The ways of integration of teaching natural sciences with professional practical training in the process of preparing medical specialists have been elaborated. It has been found that it is advisable to overcome inconsistency between separate academic disciplines by way of their integration while accounting the aspects of their selforganization. It has been established that integration of the aims of teaching natural sciences with professional training of future medical workers is based on the idea of purposefulness and motivation of teaching the fundamentals of these sciences.
Keywords: natural sciences training; natural science disciplines; doctors’ education; integration; professional practical training; professional competence; motivation; teaching content selection criteria